LA CARTA PROFÉTICA DE JAMAICA DESDE LA PERSPECTIVA DEL ORIGEN DEL CONOCIMIENTO (2016)
This article presents a brief reflection on the Charter of Jamaica, historical instrument written by Simon Bolivar, which contains a revealing political erudition and a great social sensitivity of its author, the General Bolivar. It expresses the philosophy course that he feels to defend the independence and consolidate the power of the Republic in the Spanish America, and is standard political partner of the Bolivarian thought, for Latin America.